The Influence of Social Media Influencers and Institutional Trust on Gen Z Students’ Decisions in Choosing Educational Institutions on Instagram - Refy Humairoh; Fedianty Augustinah; Dian Ferriswara (Journal of Educational Management Research, 2026)
This study aims to examine the influence of social media influencers and institutional trust on Generation Z students’ decisions in choosing educational institutions through the Instagram platform. The research employs a quantitative approach with an explanatory research design. The sample consists of 96 Generation Z respondents selected using the Cochran formula. Data were collected through a structured questionnaire using a Likert scale and analyzed using multiple linear regression techniques. The results indicate that social media influencers have a significant effect on students’ decision-making in selecting educational institutions, as evidenced by a t-value of 5.560 (p < 0.05). Institutional trust also shows a significant influence on students’ decisions, with a t-value of 4.425 (p < 0.05). Simultaneously, the F-test yields an F-value of 177.332 (p < 0.05), demonstrating that social media influencers and institutional trust collectively exert a significant impact on students’ enrollment decisions. Furthermore, the coefficient of determination (R²) of 0.617 indicates that 61.7% of the variance in students’ decision-making can be explained by the two independent variables, while the remaining 38.3% is influenced by other factors outside the research model.The findings imply that effective management of social media influencers and the strengthening of institutional trust play a crucial role in educational marketing and public relations management. Educational institutions are encouraged to optimize influencer-based digital promotion strategies while simultaneously enhancing credibility, transparency, and institutional reputation to attract Generation Z students in the digital era